The Effect of Using Storytelling Technique on Students' Speaking Skill of II Class at SMPS Plus Kasih Ibu Patumbak - Pratiwi, Tania; Zulfitri, Zulfitri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The objective of this study was to ascertain the impact of employing narrative strategies on the oral communication abilities of students at SMPS Plus Kasih Ibu Patumbak. The employed research methodology is experimental. The study population consisted of 105 students from class VII SMPS Plus Kasih Ibu Patumbak. The experimental group, consisting of 35 students from class VII-A, received instruction on storytelling techniques in narrative texts. The control group, consisting of 35 students from class VII-B, did not receive instruction on storytelling. The research was carried out using the following procedures: administering tests, providing interventions, and conducting post-tests. The examination is conducted in the form of an oral test. The researcher poses inquiries pertaining to the subject matter, and the students respond verbally. The findings indicate a notable improvement in students' oral proficiency through the utilisation of storytelling methodologies. Upon performing the data analysis, the researcher determined that the t-observation value was 3.80, whereas the t-table value was 2.00. The t-observation value (3.80) is greater than the t-table value (2.00) with a sample size of 68 and a significance threshold of α=0.5. Therefore, the alternative hypothesis (Ha) is deemed valid. Storytelling approaches have a notable impact on students' speaking abilities